A case of mr imaging detection of hemorrhages in cerebral amyloid angiopathy (Pulse, 2015)
A 70-year-old diabetic and hypertensive male patient with mild renal impairment presented with recurrent stroke. CT scan of brain demonstrated acute hemorrhagic / nonhemorrhagic infarcts in the brain. Gradient sequences in the follow-up MRI showed extensive blooming in the cortex of both cerebral hemispheres. There were multiple foci of blooming in basal ganglia and cerebellar hemispheres. Hemosiderin staining was present in posterior fossa. MR findings were consistent with extensive primary cerebral amyloid angiopathy (CAA).Pulse Vol.7 January-December 2014 p.53-55